2008
DOI: 10.1007/s12257-008-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of a quartz crystal nanobalance to the molecularly imprinted recognition of phenylalanine in solution

Abstract: A quartz crystal nanobalance (QCN) biosensor was developed for the selective determination of phenylalanine (Phe) in aqueous solutions. A Phe imprinted copolymer was synthesized using polyacrylonitrile and acrylic acid [poly(AN-co-AA)]. The copolymer was then coated on quartz crystal electrode to form complementary structures for the template recognition of Phe. The composite electrode was then used to determine Phe levels in solution. Determinations were based on frequency shifts of molecularly imprinted poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Mirmohseni et al [39] have reported the preparation of a MIP-based QCM sensor for the selective detection of phenylalanine. MIP film sensitive toward phenylalanine on the surface of the sensor was synthesized by co-polymerization of acrylonitrile (AN) and acrylic acid (AA) [poly(AN-co-AA)] in the presence of the target amino acid phenylalanine.…”
Section: Mip Based-quartz Crystal Microbalance (Qcm) Sensorsmentioning
confidence: 99%
“…Mirmohseni et al [39] have reported the preparation of a MIP-based QCM sensor for the selective detection of phenylalanine. MIP film sensitive toward phenylalanine on the surface of the sensor was synthesized by co-polymerization of acrylonitrile (AN) and acrylic acid (AA) [poly(AN-co-AA)] in the presence of the target amino acid phenylalanine.…”
Section: Mip Based-quartz Crystal Microbalance (Qcm) Sensorsmentioning
confidence: 99%
“…Due to high stability, easy synthesis and regeneration possibility, polymers, such as polyaniline, polystyrene and their derivatives, have gathered enormous attention in recent years as adsorbents. [12][13][14][15] They are being extensively employed as alternatives for conventional adsorbents and activated carbon, for exclusion of colour and toxicants from wastewater. Acid doped polyaniline (PANI) was successfully used by researchers for the removal of anionic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity is a highly important issue in the development of an effective biosensor [12][13][14]; thus, enormous efforts have been made to maximize sensitivity in various detection systems [15][16][17][18][19]. OBPs can be used to increase the sensitivity of olfactory receptor-based biosensors [20].…”
Section: Introductionmentioning
confidence: 99%